Laparoscopic removal of a fishbone migrating from the gastrointestinal tract to the pancreas. Issue 3 (19th January 2021) - Mulita, Francesk; Kehagias, Dimitris; Tchabashvili, Levan; Iliopoulos, Fotis; Drakos, Nikolas; Kehagias, Ioannis
Abstract: Laparoscopic surgery can be performed safely for the removal of a foreign body embedded in the pancreas and should be preferred instead of open surgery, whenever possible. Abstract : Laparoscopic surgery can be performed safely for the removal of a foreign body embedded in the pancreas and should be preferred instead of open surgery, whenever possible.